VANAPRASTHA WELLNESS TOURISM: A CONCEPTUAL SYNTHESIS OF BALINESE TRADITIONAL VALUE - I Gede Wiwin Suyasa; Amiluhur Soeroso; Nur Widiyanto; I Nyoman Sudiarta (Magister Tourism Study, Faculty of Tourism, Udayana University, 2023)
Humans are ancient creatures who live in the modern era; human evolution is closely related to the evolution of the natural surroundings. The concept of human connection to nature tradition of going into the forest is known almost throughout Asia by various names; in Japan, the ancient tradition of forest walks to reduce tension and mental fatigue is called Shinrin-yoku, translated in English as Forest Bathing. In ancient Bali, there was a tradition of spending one of the four stage of live (catur asrama) dealing with the forest, known as Vanaprastha. Bali have a great potential to develop eco-tourism and has no shortage of wellness retreats. This qualitative exploratory study, attempts to synthesize the concepts of forest bathing, ecotourism, wellness, and vanaprastha, as an initial proposal to mini theory development, with a typical qualitative approach adopting the five-phased cycle of data compilation, disassembling, reassembling, interpreting and concluding. Utilizing manual data analysis procedures. This study manages to disassemble concepts of the phenomena, subtract them down into distinctive elements, then reassemble the intersected elements into themes, to be then made into compounds to be interpreted and arranged as a new concept of sustainable nature and forest-based tourism aimed at improving the health of tourists through cultural healing while accelerating the capacity building of the host community on economic sustainability – practices that are geared towardslong-term economic growth, which minimize adverse impacts to social, environmental, and cultural aspects of the community. Keywords: vanaprastha wellness tourism; forest bathing; ecotourism; wellness